Fraud Triangle Dan Korupsi Pada Pemerintah Daerah di Indonesia - Rahmawati, Isna Putri; Nuruddinia, Maulia (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2021)
This study aims to test empirically the effect of fraud triangle theory at local governments in Indonesia. The sample of this study was 890 district and municipal governments all over Indonesia in 2017-2018. Data were analyzed using logistic regression analysis. This study found that the variable total regional assets can be the opportunity factor of fraud at local government. Meanwhile, regional independence, capital budget, and auditee response variables has no effect on fraud at local government.